2019
DOI: 10.1002/ecy.2596
|View full text |Cite
|
Sign up to set email alerts
|

Biotic homogenization of wetland nematode communities by exotic Spartina alterniflora in China

Abstract: Introduced species may homogenize biotic communities. Whether this homogenization can erase latitudinal patterns of species diversity and composition has not been well studied. We examined this by comparing nematode and microbial communities in stands of native Phragmites australis and exotic Spartina alterniflora in coastal wetlands across 18°of latitude in China. We found clear latitudinal clines in nematode diversity and functional composition, and in microbial composition, for soils collected from native P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 68 publications
(162 reference statements)
4
41
1
Order By: Relevance
“…In striking contrast, this study, together with our previous work in China (Zhang, Pennings, et al, 2019), found no latitudinal pattern in richness or diversity for nematodes sampled from the salt marshes in China that were dominated by introduced S. alterniflora . As a result, beta diversity increased with geographic distance (latitude) in the United States, but not in China.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In striking contrast, this study, together with our previous work in China (Zhang, Pennings, et al, 2019), found no latitudinal pattern in richness or diversity for nematodes sampled from the salt marshes in China that were dominated by introduced S. alterniflora . As a result, beta diversity increased with geographic distance (latitude) in the United States, but not in China.…”
Section: Discussioncontrasting
confidence: 99%
“…This pattern is also consistent with the general trend of decreased diversity of species overall, and of richness within most taxa, at higher latitudes (Gaston, 2000; Hillebrand, 2004; Mannion et al, 2014). Previous work along the East Coast of China found that soil nematode richness and diversity decreased with increasing latitude within wetland habitats dominated by the native grass Phragmites australis , with nematode richness about twice as high at low (22°) versus high (39°) latitudes (Zhang, Pennings, et al, 2019). Thus, this pattern of decreasing nematode diversity with increasing latitude appears to be consistent for nematode in native plants dominating coastal wetlands as well as for nematodes in terrestrial habitats (Nielsen et al, 2014; Song et al, 2017; Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations